2008
DOI: 10.1038/nature06544
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclical DNA methylation of a transcriptionally active promoter

Abstract: Processes that regulate gene transcription are directly under the influence of the genome organization. The epigenome contains additional information that is not brought by DNA sequence, and generates spatial and functional constraints that complement genetic instructions. DNA methylation on CpGs constitutes an epigenetic mark generally correlated with transcriptionally silent condensed chromatin. Replication of methylation patterns by DNA methyltransferases maintains genome stability through cell division. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
639
2
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 824 publications
(677 citation statements)
references
References 47 publications
27
639
2
8
Order By: Relevance
“…The research to date is also generally consistent with the 'environmental epigenetics' hypothesis, suggesting that environmentally-induced alteration in cell signaling pathways actively remodel DNA methylation states. These findings are also consistent with those of in vitro models, revealing stunningly dynamic regulation of DNA methylation [67,68,[82][83][84]. Although there are a limited range of research models in which this issue has been directly addressed, the evidence in rodents is consistent with the idea that nutritional signals as well as variations in parent-offspring interactions can influence the methylation state of specific genes, which then mediate parental effects on phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…The research to date is also generally consistent with the 'environmental epigenetics' hypothesis, suggesting that environmentally-induced alteration in cell signaling pathways actively remodel DNA methylation states. These findings are also consistent with those of in vitro models, revealing stunningly dynamic regulation of DNA methylation [67,68,[82][83][84]. Although there are a limited range of research models in which this issue has been directly addressed, the evidence in rodents is consistent with the idea that nutritional signals as well as variations in parent-offspring interactions can influence the methylation state of specific genes, which then mediate parental effects on phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…14,15 This important pathway for active DNA demethylation has been thought to be involved in a number of prominent biological processes. 5,6,10,11 Early and recent studies suggested that active and replication-independent DNA demethylation might be a rapid process. 10,11 The radically altered methylation, as observed in replication-independent demethylation of the paternal genome in zygotes, may complete within hours.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Les facteurs épigénétiques étalent leurs effets sur la structure de la chromatine sur des échelles de temps variées allant de la minute, au cours de la signalisation par un récepteur, à des années pour la mémoire métabolique, ou à des générations pour les perturbations environnementales [38,40]. Ainsi, l'ADN subit des cycles de méthylation/ déméthylation indiquant qu'une marque « stable » d'activité génique peut toutefois être modulée par des facteurs de transcription et répondre dynamiquement à des signaux de l'environnement [41]. Contrairement à la séquence génétique, unique et stable dans toutes les cellules, les profils épigénétiques varient d'un type cellulaire à l'autre au sein d'un même tissu, voire même de la partie apicale à la partie distale d'un même tissu.…”
Section: Réversibilité Des Marques Ou Réversibilité Des éTats Phénotyunclassified